Anmeldelser - Rosenberg, Herbert (Danish Yearbook of Musicology, 1976)
Review of: Carl Nielsen: The Complete Symphonies. London Symphony Orchestra/ Ole Schmidt. Unicorn RHS 324-330. Carl Nielsens symfonier og andre orkesterværker. Radiosymfoniorkestret/ Herbert Blomstedt. HMV SLS 5027.